Measuring ROI in environment, health, and safety : a guide to evaluating EHS programs, with cases studies - Phillips, Jack J., 1945-; Phillips, Patricia Pulliam; Pulliam, Al (Hoboken, New Jersey ; Salem, Massachusetts : Wiley-Scrivener, 2014)
"Within an organization, the responsibilities for environment, health, and safety are often under the direction of the same executive team in an organization. This new book shows how to measure the success of all types of programs and projects involving environment initiatives, health related programs for employees and citizens, and various safety programs in all types of settings. It also explains how to report results by using a step-by-step approach"--
"This new book shows how to measure the success of all types of programs and projects involving environment initiatives, health related programs for employees and citizens, and various safety programs in all types of settings. It also explains how to report results by using a step-by-step approach"--
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Environmental health -- Planning; Health promotion -- Evaluation; Environmental engineering; SCIENCE / Chemistry / Organic; Environmental engineering; Environmental health -- Planning; Health promotion -- Evaluation; Electronic books; Electronic books